Bahan Baku Plastik Polystyren - Budi Utami (Jurnal Kimia dan Kemasan, 1987)
Polystyren is linear polymer which thermoplastic made with syntesa from one or more monomer eg : styren, aerylonitril and butadien. The ·bases of making polystyren is polymeritation reaction. Polymeritation have 5 bypes, each type has characteristicand used difficult. Polymeritation process have variaty technique where it is goodness and likensess.